Dinuclear Gold(I) Pyrrolidinedithiocarbamato Complex: Cytotoxic and Antimigratory Activities on Cancer Cells and the Use of Metal-Organic Framework - Sun, R.W.Y.; Zhang, M.; Li, D.; Zhang, Z.F.; Cai, H.; Li, M.; Xian, Y.J.; Ng, S.W.; Wong, A.S.T. (2015)
A dinuclear gold(I) pyrrolidinedithiocarbamato complex (1) with a bidentate carbene ligand has been constructed and shows potent in vitro cytotoxic activities towards cisplatin-resistant ovarian cancer cells A2780cis. Its rigid scaffold enables a zinc(II)-based metal-organic framework (Zn-MOF) to be used as a carrier in facilitating the uptake and release of 1 in solutions. Instead of using a conventional dialysis approach for the drug-release testing, in this study, a set of transwell assay-based experiments have been designed and employed to examine the cytotoxic and antimigratory activities of 1@Zn-MOF towards A2780cis.